The Role of Language and Culture in Postgraduate International Students’ Academic Adjustment and Academic Success: Qualitative Insights from Malaysia - Nachatar Singh, Jasvir Kaur; Jack , Gavin (Journal of International Students, 2021)
How do language and culture pose adjustment challenges that hinder the academic success of postgraduate international students? This article answers this question based on a thematic analysis of 55 semi-structured qualitative interviews conducted with postgraduate international students and academic and professional staff members at a Malaysian research-intensive public university. The results show that language and culture are influential in a range of academic (language, supervision, research training) and social (group work, friendship) adjustment challenges. The analysis highlights how these challenges hinder academic success as a result of limited or frustrated pathways for students’ linguacultural development. We conclude that future academic research and university policy to support postgraduate international students may pay greater attention to crosscultural, linguistic, and linguacultural issues.